Strengthening the Enforcement of the Advocate's Code of Ethics as an Effort to Enhance Professionalism in the Profession - Ilham Khafid Alfarozi; Anand Pamuji Gusti; Afrizal Anindya Helvin; Wahyu Saputro; Agus Joko Purnomo; Agatha Jumiati (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This article aims to analyze the strengthening of the enforcement of the advocate's code of ethics as an instrument in enhancing the professionalism of the legal profession in Indonesia. The main issue examined is how the regulation of the advocate's code of ethics within the Indonesian legal system and the effectiveness of its enforcement in realizing professional standards. This research uses a normative juridical method with a legislative and conceptual approach, based on the analysis of Law Number 18 of 2003 concerning Advocates, the Indonesian Advocate Code of Ethics, and relevant legal doctrines. The research results show that normatively, the regulation of the advocate's code of ethics has a strong and comprehensive legal foundation, encompassing the principles of independence, integrity, confidentiality, and professional responsibility. However, in practice, the enforcement of the code of ethics still faces various obstacles, such as weak supervision, fragmentation of the lawyer organizations, and the suboptimal role of the Honorary Council in upholding professional discipline. This condition creates a gap between norms and implementation, which affects the professionalism of lawyers and public trust. Therefore, it is necessary to strengthen the enforcement of the code of ethics thru regulatory harmonization, increased transparency and accountability, and the strengthening of an ethical culture within the profession. With effective and consistent enforcement, the advocate's code of ethics is expected to function optimally as an instrument for enhancing professionalism and supporting an integrity-based judicial system.